Inovasi program pengendalian malaria menuju eliminasi malaria di Kabupaten Fakfak, Papua Barat: Malaria Control Program Innovation Towards Malaria Elimination in Fakfak District, West Papua - Rina Marina; Shinta; Helper Sahat P Manalu; Alfons M. Letelay; Muhammad Fajri Rokhmad; Tri Isnani (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Malaria control in Indonesia has been facing various challenges and obstacles, especially in Eastern Indonesia. Several strategies have been carried out to achieve national elimination by 2030. This study aims to explore innovative strategies for controlling malaria in Fakfak Regency, West Papua Province which is one of the malaria endemic areas in eastern Indonesia. This type of research is a qualitative study using in-depth interviews with malaria program managers (n=6). The interview process was recorded through the zoom-meeting application and then transcription of the interview results was used to conduct content analysis. The results showed that the Bela Kaca Innovation (Bebas Malaria Kampung Bercahaya), which was initiated by the Fakfak Regency Health Office, hassucceeded significantly in reducing malaria cases in the last 5 years. This program fights malaria from village to village by involving all parties in the Malaria Center. The innovation of Bela Kaca is carried out by attacking and defending strategies. The attacks are carried out intensively in villages that had 5 or more malaria cases within two months by mass screening, indoor residual spraying (IRS), surveys of insecticide-treated mosquito nets and vector control until cases become zero. The survival strategy is carried out if there are no malaria cases, then surveillance is carried out strictly, if cases are found, then the 1-2-5 method is used. In conclusion, Bela Kaca control innovation can be one of the efforts to accelerate malaria elimination that is supported by the community and stakeholders